2022
DOI: 10.3390/app12073489
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Emission Analysis of Fracture and Size Effect in Cementitious Mortars

Abstract: The size effect is a phenomenon where the strength and the ductility of a material depend on the size of the structure. Investigating size effects and related crack formation in brittle materials requires advanced monitoring methods. The aim of this research is to experimentally investigate the impact of size effect with the acoustic emission (AE) technique. Brazilian splitting tests with AE monitoring were performed on cement-based mortar cylinders of three sizes. It was found that in addition to the size, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…However, after passing the critical stage (after the 14 th cycle) the gradually growing damage was noticed by the progressively increasing AE activity and DIC-tensile deformation (see Figure 2 a) and Figure 2 b)). It was also observed that fatigue loading causes a relatively more gradual rise in AE activity than the steep rise in AE activity identified for monotonic Brazilian splitting tests on similar samples [3,7].…”
Section: Fatigue Damage Analysis From Dic Displacements and Ae Parame...mentioning
confidence: 80%
“…However, after passing the critical stage (after the 14 th cycle) the gradually growing damage was noticed by the progressively increasing AE activity and DIC-tensile deformation (see Figure 2 a) and Figure 2 b)). It was also observed that fatigue loading causes a relatively more gradual rise in AE activity than the steep rise in AE activity identified for monotonic Brazilian splitting tests on similar samples [3,7].…”
Section: Fatigue Damage Analysis From Dic Displacements and Ae Parame...mentioning
confidence: 80%
“…A cement mortar was used for all test specimens, with a composition of 533 kg/m³ CEMII/B (S-L) 32.5 N; 1600 kg/m³ river sand with a maximum aggregate size of 4 mm and 0/2 grain size curve distribution according to EN 13139 and 266.5 l/m³ water, resulting in a 0.5 W/C ratio. Conditions of sample preparation and curing are described in [7]. For direct tensile tests, cylinders with 50 mm in diameter and 150 mm in length are cored (drilled) from a 150 mm x 150 mm x 150 mm mortar cube.…”
Section: Materials and Mechanical Testsmentioning
confidence: 99%
“…4 b), d) and f), where there is an increase of AE events with low peak frequencies near the peak load (90 to 100%) and almost no AE activity at the post-peak stage (100 to 90%). This is mainly because for larger samples, there is a sudden (brittle) crack propagation that will intensify the effect of attenuation and generation of shear noise [7]. The histogram of the peak frequencies of all of the AE events in the friction tests is shown in Fig.…”
Section: Ae Peak Frequencymentioning
confidence: 99%
“…Researchers also used AET to quantify the size of the FPZ [1,[23][24][25][26][27]. Ohno, et al [28] used the mean and the standard deviation of the x-coordinate values of AE source locations to define the width of the FPZ as the region with one standard deviation from the mean value.…”
Section: Introductionmentioning
confidence: 99%
“…Ohno, et al [28] used the mean and the standard deviation of the x-coordinate values of AE source locations to define the width of the FPZ as the region with one standard deviation from the mean value. Alam, et al [27] used the cumulative located AE events plot and evaluated the width at arbitrary horizontal lines found at 20 % of the peak, and this approach was adopted in our previous work on monotonic loading [25]. Otsuka and Date Preprint submitted to Construction and Building Materials 1st August 2023 [24] found that 45 % of the total number of AE events made up only 0.5 % of the total AE energy.…”
Section: Introductionmentioning
confidence: 99%